2016
DOI: 10.1186/s12967-016-0797-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cancer cell growth by ruthenium complexes

Abstract: BackgroundPrevious studies suggest that certain transition metal complexes, such as cisplatin, are efficacious for treating various cancer types, including ovarian, lung, and breast.MethodsIn order to further evaluate ruthenium (Ru) complexes as potential anti-cancer agents, we synthesized and evaluated Ru-arene complexes. Two complexes with the general formula [Ru (η6-p-cym) (N–N) Cl]+ were tested for their abilities to inhibit cancer cells.ResultsThe complex with o-phenylenediamine as the N–N ligand (o-PDA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…Thus, complex (2) was selected to be further investigated using in vitro and in vivo assays. In accordance with our results, another study using a ruthenium arene o-PDA complex, [(p-cym)Ru(o-pda)Cl]PF 6 (o-PDA), demonstrates that after 48 h of incubation the inhibition of the proliferation of MDA-MB-231 cells (83 μM) was more than three times higher than in MCF-10A cells (> 260 μM) showing that it also exhibits selectivity for tumor cells [46]. Different studies have shown that ruthenium complexes with similar structure to the complex (2) also have cytotoxic activity against different tumor cells.…”
Section: In Vitro Assayssupporting
confidence: 91%
“…Thus, complex (2) was selected to be further investigated using in vitro and in vivo assays. In accordance with our results, another study using a ruthenium arene o-PDA complex, [(p-cym)Ru(o-pda)Cl]PF 6 (o-PDA), demonstrates that after 48 h of incubation the inhibition of the proliferation of MDA-MB-231 cells (83 μM) was more than three times higher than in MCF-10A cells (> 260 μM) showing that it also exhibits selectivity for tumor cells [46]. Different studies have shown that ruthenium complexes with similar structure to the complex (2) also have cytotoxic activity against different tumor cells.…”
Section: In Vitro Assayssupporting
confidence: 91%
“…As one of the most promising alternatives to platinum-based chemotherapeutics are Ru(II) and Ru(III) complexes. They possess unique multifunctional biochemical properties and exhibit lower toxic effects than platinum-based chemotherapeutics [14,15]. In cancer cells, trivalent Ru complexes are speculated to be reduced by cellular reductants, e.g., ascorbates, to their more active divalent form.…”
Section: Introductionmentioning
confidence: 99%
“…It can also activate Nrf2 pathway for apoptosis primarily through the activation of caspase [ 49 ]. Another important report suggest that Ru-arene complexes are promising anti-cancer drugs that inhibit progression and metastasis by blocking multiple processes of cancers [ 50 ]. These Ru-arene complexes also inhibited growth factor productions such as VEGF-A, PDGF-AA, and GM-CSF proteins at the transcriptional levels.…”
Section: Resultsmentioning
confidence: 99%